Enhancing Efficiency in Student Attendance Recording through Implementation of a Digital Presence System: A Field Study in Elementary Schools - Fahmi Syahidi; Iman Subasman; Ade Aspandi; Mila Dita Khotimah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Student attendance management is an essential component of school administration that affects both learning discipline and institutional accountability. This study aimed to examine the implementation of a digital presence system to improve the efficiency and accuracy of attendance recording at SDN Taman Kalijaga Permai. The research employed a qualitative descriptive approach through field observation, in-depth interviews, and documentation to obtain a comprehensive understanding of the digital system’s impact on administrative performance and classroom routines. Data were collected from teachers, students, and school administrators who actively used the digital attendance platform based on QR code technology. The findings revealed that the digital presence system significantly reduced the time needed for attendance recording and minimized manual errors in data entry. Teachers reported improved convenience and accuracy, while students demonstrated increased punctuality and accountability. Furthermore, the school administration benefited from easier access to real-time attendance reports, which supported transparent data management and decision-making. These results indicate that the use of digital presence systems contributes to both administrative efficiency and behavioral discipline among students. The study implies that successful technology adoption in elementary schools depends on teacher readiness, infrastructure support, and digital literacy. Schools are encouraged to integrate continuous training and stakeholder collaboration to ensure system sustainability. Future research could expand to multiple schools or examine the long-term effects of digital attendance on student performance and engagement.